Магнитное поле и давления, возбуждаемые одновитковым индуктором в угловом изгибе листовой заготовки - Батыгин, Юрий Викторович; Сериков, Георгий Сергеевич (НТУ "ХПИ", 2006)
Проведен теоретический анализ электродинамических процессов в индукторной системе, предназначенной для формовки углов в предварительно изогнутых металлических листах. Проведенные расчёты осветили возможные варианты конструктивного исполнения индукторной системы, позволяющие в конечном итоге повысить эффективность.

Electrodynamic processes in an inductor system intended for bend molding on prebent metal plates are theoretically analyzed. Analytical expressions for magnetic field strength are derived. Their validity is verified by means of limiting process to known and earlier-described solutions. Calculations made for the inductor system reveal feasible variants of the system design which allow higher efficiency by increasing force action efficiency in the bend molding zone and decreasing pressure on the adjacent surface of the sheet billet.
Magnetic field and pressure excited by a single-turn inductor in a sheet-billet bend
Keywords: электродинамические процессы; гиперпластичность; магнитно-импульсная обработка металла; magnetic pulse metal working; inductor system; bend molding; sheet billet